Pengaruh Model Pemebelajaran Contextual Teaching and Learning (CTL) Berbasis Kearifan Lokal Terhadap Hasil Belajar Seni Rupa Kelas V SD Negeri 101767 Tembung - Sushmita Marina Angel; Putra Afriadi; Nurhairani; Try Wahyu Purnomo; Yusra Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model integrated with local wisdom on the visual arts learning outcomes of fifth-grade students at SD Negeri 101767 Tembung. The study was motivated by students' low academic achievement in visual arts, evidenced by mid-semester summative data showing a mastery rate of only 36.7%. Conventional and monotonous learning activities limited to simple drawing media had negatively impacted student motivation and creativity. A quantitative approach with a one-group pretest-posttest design was employed. The research subjects consisted of all 30 fifth-grade students at SD Negeri 101767 Tembung in the 2025/2026 academic year. Data were collected using a 15-item multiple-choice test that had been validated and proven reliable (Cronbach's Alpha = 0.91). Data analysis included the Shapiro-Wilk normality test and paired sample t-test. The results demonstrated a significant increase in mean scores from 51.7 (pretest) to 84.6 (posttest). Hypothesis testing yielded a significance value (Sig. 2-tailed) of < 0.001, leading to the rejection of H₀ and acceptance of Hₐ. These findings confirm that the CTL model integrated with local wisdom significantly improves students' visual arts learning outcomes, particularly in the topic of creating decorative motif patterns based on Batak Toba cultural heritage.